2006
DOI: 10.1103/physrevlett.97.013901
|View full text |Cite
|
Sign up to set email alerts
|

Do Solitonlike Self-Similar Waves Exist in Nonlinear Optical Media?

Abstract: We show analytically that bright and dark spatial self-similar waves can propagate in graded-index amplifiers exhibiting self-focusing or self-defocusing Kerr nonlinearities. The intensity profiles of the novel waves are identical with those of fundamental bright or dark spatial solitons supported by homogeneous passive waveguides with the same type of nonlinearity. Thus, we reveal a previously unnoticed connection between spatial solitons and self-similar waves. We also suggest that the discovered self-simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
127
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(130 citation statements)
references
References 20 publications
(18 reference statements)
2
127
0
1
Order By: Relevance
“…We have observed that the second-and thirdorder RWs transform to first-order RW-like structures when a parameter appearing in the harmonic trap (timeindependent and time-dependent traps) is varied. We have then analyzed the characteristics of triplet and sextet patterns of matter RWs for (1). We have also constructed one-breather and two breather solutions of (1).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have observed that the second-and thirdorder RWs transform to first-order RW-like structures when a parameter appearing in the harmonic trap (timeindependent and time-dependent traps) is varied. We have then analyzed the characteristics of triplet and sextet patterns of matter RWs for (1). We have also constructed one-breather and two breather solutions of (1).…”
Section: Discussionmentioning
confidence: 99%
“…(1). In this section we analyze how the breather structures get modified in the condensates when we vary the strength of the external trap parameter.…”
Section: Characteristics Of Breathersmentioning
confidence: 99%
See 2 more Smart Citations
“…The NLS equation describing light propagation in optics [11] with real external potentials or/and gain-andloss distributions has been investigated [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] since the refractive index of the optical waveguide can be complex [29,30]. It is surprising to find that if the complex refractive index satisfies the property of the paritytime (PT ) symmetry [31], that is, if the real and imaginary parts of the refractive index are the even and odd functions of spatial position, respectively, then the propagation constant of the light can still be in all-real spectrum range, hence admitting stationary beam transmission [32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%